Passively Q-switched fibre laser based on a saturable absorber of siloxane. (18th July 2018) - Pan, Honggang; Zhang, Ailing; Tong, Zhengrong; Bai, Yangbo; Guo, Qing
Abstract: A passively Q-switched fiber laser using a novel saturable absorber (SA) of Siloxane has been demonstrated. The modulation depth of the SA is measured to be 4.87%. Based on such an SA, the Q-switched operation in the laser has been achieved. The average output power of the Q-switched fiber laser is 0.78 mW with a pulse repetition rate of 21.3 kHz. The pulse energy goes up to 36.62 nJ when the pump power of the laser is 200 mW. The Q-switched laser exhibits the performances of self-starting, good stability, and high pulse energy. To the best of our knowledge, it is the first demonstration of the passively Q-switched laser based on a siloxane SA.